2007
DOI: 10.1007/s12035-007-0002-5
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids and Gliomas

Abstract: Cannabinoids, the active components of Cannabis sativa L., act in the body by mimicking endogenous substances--the endocannabinoids--that activate specific cell surface receptors. Cannabinoids exert various palliative effects in cancer patients. In addition, cannabinoids inhibit the growth of different types of tumor cells, including glioma cells, in laboratory animals. They do so by modulating key cell signaling pathways, mostly the endoplasmic reticulum stress response, thereby inducing antitumoral actions s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 64 publications
1
61
0
Order By: Relevance
“…Recently, numerous studies have evidenced the role of cannabinoids as potential anti-tumoral drugs owing to their ability to reduce tumor in different animal models, including glioma, 6 breast cancer 7,8 and prostate cancer. 9,10 Recent research has also reported that the synthetic cannabinoid WIN-55 212-2 inhibits HCC growth.…”
mentioning
confidence: 99%
“…Recently, numerous studies have evidenced the role of cannabinoids as potential anti-tumoral drugs owing to their ability to reduce tumor in different animal models, including glioma, 6 breast cancer 7,8 and prostate cancer. 9,10 Recent research has also reported that the synthetic cannabinoid WIN-55 212-2 inhibits HCC growth.…”
mentioning
confidence: 99%
“…THC but not CBD has been shown to engage cannabinoid receptors to promote tumor cell death (16,23,34). Thus, THC triggers the accumulation of de novo-synthesized ceramide, which leads in turn to stimulation of autophagy and apoptosis (15).…”
Section: Combined Treatment With Thc and Cbd Greatly Enhances Glioma mentioning
confidence: 99%
“…Among these therapeutic applications, cannabinoids are being investigated as antitumoral agents (11,12). Thus, cannabinoid administration curbs the growth of several types of tumor xenografts in rats and mice (11,12) including gliomas (13)(14)(15)(16). On the basis of this preclinical evidence, a pilot clinical trial has been recently conducted to investigate the antitumoral action of THC on recurrent gliomas (17).…”
mentioning
confidence: 99%
“…The fact that lipoprotein-derived endocannabinoids help to repress such an important tumor-promoting pathway suggests new possibilities to explain the link between disturbed lipoprotein metabolism and cancer risk [32]. In fact, cannabinoids block the growth of many tumors known to depend on Hh signaling [33,34,35,36,37,38,39,40].…”
Section: Spectrometry (Ms/ms) and Thin Layer Chromatography (Tlc) Msmentioning
confidence: 99%